The Gut Microbiome Is Altered in Postmenopausal Women With Osteoporosis and Osteopenia. (19th January 2021) - Rettedal, Elizabeth A; Ilesanmi‐Oyelere, Bolaji L; Roy, Nicole C; Coad, Jane; Kruger, Marlena C
ABSTRACT: Osteoporosis and its precursor osteopenia are common metabolic bone diseases in postmenopausal women. A growing body of evidence suggests that the gut microbiota is involved in the regulation of bone metabolism; however, there are few studies examining how gut microbiomes in osteoporosis and osteopenia may differ from those in healthy individuals. The aim of this study was to characterize the diversity, composition, and functional gene potential of the gut microbiota of healthy, osteopenic, and osteoporotic women. Body composition, bone density, and fecal metagenomes were analyzed in 86 postmenopausal women. The women were classified as healthy, osteopenic, or osteoporotic based on T ‐scores. The taxonomic and functional gene compositions of the microbiome were analyzed using shotgun metagenomic sequencing. Both osteoporotic and osteopenic taxonomic compositions were found to be significantly different from healthy participants. Linear discriminant‐analysis effect‐size analyses identified that healthy participants had more unclassified Clostridia and methanogenic archaea ( Methanobacteriaceae ) than in both osteoporotic and osteopenic participants. Bacteroides was found to be more abundant in osteoporosis and osteopenia groups. Some KEGG pathways, including carbohydrate metabolism, biosynthesis of secondary metabolites, and cyanoamino acid metabolism, were found to be more abundant in both osteoporosis and osteopenia. These results show that osteoporosis and osteopenia alter the gut microbiome of postmenopausal women and identify potential microbial taxonomic and functional pathways that may be involved in this disease. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.